THE USE OF REALISTIC MATHEMATIC EDUCATION APPROACH TO IMPROVE LEARNING OUTCOMES ABOUT TWO-DIMENSIONAL SHAPES AT SDN PANDEGLANG 14 - Asni Asni; Urip Kwilangga (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
The background of this research is the students' difficulties in solving two-dimensional shapes, and the students' learning outcomes are still low. Then in the learning process, requires an approach that can improve students' activity and students learning outcomes, namely the RME approach. In this research, the subject of Mathematics learning activities with the RME approach were the 24 students of 6th-grade. In this study uses the model of Classroom Action Research (CAR). Based on research with a Realistic Mathematics Education (RME) approach on the material of two-dimensional shapes in 6th-grade has a great influence on improving student understanding. The results of the study showed that there were student activities scores using the RME approach starting from cycle I with the score of 1.9, in cycle II with a score of 2.9, and in cycle III with the score 3.9. On pre-cycle student learning scores got 4.2, cycle I 5.5, cycle II 6.8 and cycle III got a score of 8.2. So, it can be concluded that the use of the RME approach in mathematics learning about two-dimensional shapess can improve student activities and student learning outcomes with good improvement. Keywords: Realstic Mathematic Education (RME), Learning Outcomes